Religiosity and Digital Piracy: An Empirical Examination. Issue 1 (2nd January 2016) - Casidy, Riza; Phau, Ian; Lwin, Michael
ABSTRACT: This study aims to examine the relationship between religiosity, attitudes to digital piracy, and behavioral intention. A total of 400 questionnaires were completed by members of a Christian mega-church in Indonesia. Cluster analysis and MANOVA were employed to determine whether there are significant differences between the less religious, moderately religious, and highly religious respondents in their attitude to digital piracy and behavioral intention. This study provides empirical evidence that highly religious respondents have a stronger attitude against digital piracy and are more willing to stop purchasing pirated media compared to the less religious and moderately religious respondents.